Pelatihan scratch programming untuk anak-anak SD Umeanyar - Gede Beny Indrawan; I Gusti Andiani Octavia; Gede Arya Ardivan Pratama Saputra; I Gede Krishna Adi; I Gusti Lanang Agung Andrayuga; Luh Joni Erawati Dewi (Unri Conference Series: Community Engagement, 2021)
The ability to read, write, and arithmetic is something that must be mastered by all students. Computational thinking is considered as one of the basic competencies to complete these skills. After entering a higher level students will be introduced to learning that involves technology and it requires sufficient understanding to easily understand the basics of computer technology logic. Some elementary schools still do not use technology to encourage students' computational thinking skills. During the Covid-19 pandemic, students had difficulty understanding learning materials and decreased student interest in learning. The elementary school curriculum in Umeanyar Village has not implemented computational thinking, this makes it difficult for students to understand the logic of computer technology at higher school levels and material concepts that require critical thinking logic. Therefore, the purpose of this activity is (1) to educate students on how to use the scratch application as a method to introduce mathematical and computational thinking in elementary schools and (2) to provide hands-on experience for students to introduce simple programming concepts by creating animation projects and games and fostering cooperation between each other so that the learning atmosphere is more interesting. These objectives can be achieved by means of preliminary studies, implementation of training and mentoring, and evaluation. After providing material and training, students are invited to make a games and animation project for 3 meetings which are held every Saturday. The results obtained by students after participating in this training are increased understanding and experience of how to use computers and students can create animations and simple games with the scratch application. Previously, students were still unfamiliar with using computers and computer applications and had difficulty understanding how to operate the software. Students still need assistance and support from the surrounding environment in implementing this training. For this reason, village heads and schools need to work together to support their students through various training activities that provide knowledge and insight for the next level of education. As for the universities that can help realize the program.